Traumatic Dental Injury to Primary Teeth - Obehi O Osadolor (Update Dental College Journal, 2023)
Background: Traumatic dental injuries (TDI) in primary teeth can significantly impact the quality of life of affected children, often leading to discomfort and pain. These injuries encompass various diagnostic categories, such as concussion, luxation injuries, uncomplicated crown fractures, complicated crown fractures, and avulsion.